The Influence of Technology Adoption, Sharia Financial Behavior, Pocket Money, and Social Environment on Halal Lifestyle (Case Study of Febi UINSU Students) - Ezika Aquilera Sitio; Rahmi Syahriza; Imsar Imsar (Indonesian Journal of Islamic Economics and Finance, 2026)
The rapid development of digital technology has significantly transformed consumption patterns and financial behavior in society, particularly among university students. At the same time, increasing awareness of Islamic principles has encouraged the adoption of a halal lifestyle in various aspects of daily life. This study aims to analyze the influence of technology adoption, Islamic financial behavior, allowance, and social environment on the halal lifestyle of students at the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra (FEBI UINSU). This research employed a quantitative approach using primary data collected through questionnaires distributed to 100 students, selected from a total active population of approximately 4,300 FEBI UINSU students using the Slovin sampling technique with a 10% margin of error. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing through t-tests and F-tests. The results indicate that technology adoption, Islamic financial behavior, allowance, and social environment have a positive and significant influence on students' halal lifestyle. Among these variables, the social environment was found to be the most dominant factor affecting the implementation of a halal lifestyle. Furthermore, all four variables simultaneously exert a significant influence on students' halal lifestyle. These findings suggest that the effective utilization of technology, the application of Islamic financial principles, proper allowance management, and a supportive social environment can enhance the adoption of a halal lifestyle among university students.